PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS MOODLE MATERI PENGUKURAN PANJANG KELAS IV SEKOLAH DASAR - Aliffirda Zulinar; Iva Sarifah; Andi Ali Saladin (Program Studi PGSD Universitas Flores, 2022)
This study aims to develop student worksheets for measuring length for grade IV Elementary Schools based on Moodle.This research is a development research using the ADDIE model. Data in this study were obtained through questionnaires and interviews. The subjects of this study were primary school students grade IV-B at SDN Baru 08 Pagi. This study involved three experts as validators of media eligibility, including media experts, content experts, and language experts. The results of these study indicate that the development of student worksheet based on Moodle has a significant level of eligibility assessment. The results of the validation of the content experts showed the eligibility with a percentage of 91%, media experts with 85% and language experts at 90% of which all three were categorized in the